1977
DOI: 10.1113/jphysiol.1977.sp012116
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between longitudinal and circular muscle in intestine of cat

Abstract: SUMARY1. Slow waves recorded from isolated longitudinal muscle averaged 13 mV and had slow rate of rise (0.04 V/sec) whereas when recorded from intact segments the amplitude averaged 27 mV and the rate of rise was more rapid (0.09 V/sec), often with a notch between the initial peak and the plateau. Membrane potentials of longitudinal muscle were similar in isolated and intact preparations (-66 mV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
2

Year Published

1977
1977
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 16 publications
2
26
2
Order By: Relevance
“…The RMP gradient is impaired almost consistently in all studies that have used the mutant animals, separated one of the plexi from the circular muscle layer, or incubated naïve tissues with ACK2 or methylene blue (8,34,36,45,74,100,105,130,141,143,183). The resulting RMP is depolarized closer to that of the smooth muscle cells near the myenteric plexus in the colon and the submucosal plexus in the stomach and the small intestine.…”
Section: The Roles Of Icc In the Generation And Propagation Of Slow Wmentioning
confidence: 95%
See 1 more Smart Citation
“…The RMP gradient is impaired almost consistently in all studies that have used the mutant animals, separated one of the plexi from the circular muscle layer, or incubated naïve tissues with ACK2 or methylene blue (8,34,36,45,74,100,105,130,141,143,183). The resulting RMP is depolarized closer to that of the smooth muscle cells near the myenteric plexus in the colon and the submucosal plexus in the stomach and the small intestine.…”
Section: The Roles Of Icc In the Generation And Propagation Of Slow Wmentioning
confidence: 95%
“…3) Several studies during the 1960s and later found that the separation of the longitudinal muscle layer from the small intestine suppresses the slow-wave activity in the remaining circular smooth muscle cells (34,35,124,159). Initially, this finding had led to the conclusion that the longitudinal smooth muscle cells generate and propagate slow waves, and they also drive the slow waves in the circular smooth muscle cells.…”
mentioning
confidence: 99%
“…The mechanism of slow wave propagation in gastrointestinal circular muscles has been investigated before (Kobayashi, Nagai & Prosser, 1966;Bortoff & Sachs, 1970;Connor, Kreulen, Prosser & Weigel, 1977;Connor, Mangel & Nelson, 1979;Bortoff et al 1981). Bortoff and co-workers, using volume recordings, reported that intestinal slow waves spread electrotonically through the thickness of the circular muscle.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed by some authors that slow waves orginate from the longitudinal muscle cells and are transmitted to the circular muscle cells through passive electrotonic coupling (Bortoff, 1961(Bortoff, , 1965(Bortoff, , 1976Connor et al 1977). One aspect of this hypothesis was tested directly by comparing the size of electrotonic potentials between cells of the two layers at the same site.…”
Section: Discussionmentioning
confidence: 99%
“…The longitudinal muscle cells display constant spiking activity and have a lower membrane potential than the circular muscle cells in both the guinea-pig small intestine (Suzuki & Kuriyama, 1975) and the rabbit jejunum (Kitamura, 1978). It has been suggested by some authors (Bortoff, 1961(Bortoff, , 1965Connor, Kreulen, Prosser & Weigel, 1977) that the two muscle layers of the small intestine are well coupled electrically and that slow waves originate from the longitudinal muscle and spread passively into the circular muscle. Some aspects of this hypothesis were tested directly in this study by comparing the effects of temperature and external stimulation on the slow wave activity of the two muscle layers, as well as the intrinsic neural factors that affect their activity.…”
Section: Introductionmentioning
confidence: 99%